2008
DOI: 10.1111/j.1467-9701.2008.01129.x
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Direct Investment, Domestic Investment and Economic Growth in China: A Time Series Analysis

Abstract: In this paper, we investigate the causal link between foreign direct investment (FDI), domestic investment and economic growth in China for the period 1988-2003. Towards this purpose, a multivariate VAR system with error correction model (ECM) and the innovation accounting (variance decomposition and impulse response function analysis) techniques are used. The results show that while there is a bi-directional causality between domestic investment and economic growth, there is only a single-directional causalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
120
5
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(140 citation statements)
references
References 24 publications
14
120
5
1
Order By: Relevance
“…10 An exception is the work of Tang et al (2008Tang et al ( , pp. 1302) who study the Chinese economy and argue that their measure of domestic investment does not include any type of foreign investment.…”
Section: Datamentioning
confidence: 98%
See 1 more Smart Citation
“…10 An exception is the work of Tang et al (2008Tang et al ( , pp. 1302) who study the Chinese economy and argue that their measure of domestic investment does not include any type of foreign investment.…”
Section: Datamentioning
confidence: 98%
“…Other scholars find that FDI stimulates (or crowds in) private domestic investment (Al-Sadig, 2013;Ramirez, 2011;Ndikumana and Verick, 2008;Tang et al, 2008;de Mello, 1999;Bosworth and Collins, 1999;Borensztein et al, 1998). Several scholars find mixed evidence when using several lags for FDI or when splitting the country sample according to geographic region (Adams (2009); Apergis et al (2006); Agosin and Mayer (2000); Misun and Tomsik (2002); Agosin and Mayer (2000)), or find no effect of FDI on domestic investment (Lipsey (2000)).…”
Section: Introductionmentioning
confidence: 99%
“…Similar results are found in the study of China. They found that FDI has a causal impact on the economy of China, moreover FDI is encouraging domestic investment in China (Tang, Selvanathan, & Selvanathan, 2008 After going through the literature of the conclusion is that the causality results on FDI and economic growth are still diverse and unconvincing. Most of the studies show their results of unilateral causality some other shows their results of bilateral and some of the studies show their results of ambiguous.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The results of this study showed that FDI had a strong and positive effect on economic growth. Tang et al [6] investigated the causal link between FDI and economic growth in China for the period of 1988-2003 using a multivariate Vector Auto-regression (VAR) system, and found single-directional causality from FDI to GDP in China. Hong [7] employed Generalized Method of Moments (GMM) to evaluate the effect of FDI on economic growth in China, and found that FDI exerted a positive impact on the economic growth during the period of 1994-2010.…”
Section: Literature Overviewmentioning
confidence: 99%